FLR 2018
DOI: 10.14786/flr.v6i3.379
|View full text |Cite
|
Sign up to set email alerts
|

A multi-componential methodology for exploring emotions in learning

Abstract: Studies on emotions in learning are often based on interviews conducted after the learning. These do not capture the multi-componential nature of emotions, nor how emotions are related to the processes of learning. We see emotions as dimensional, multi-componential responses to personally meaningful events and situations. In this methodologically advanced pilot study we developed a multi-componential methodology, capable of providing complementary information on emotions in professional learning. For this purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 50 publications
(112 reference statements)
3
6
0
Order By: Relevance
“…EDA data followed a significant linear trend corresponding to HR data, which is, considering the self-report results, in line with our second hypothesis. Prior research (e.g., Eteläpelto et al, 2018 ; Kreibig, 2010 ) showed that high EDA values are indicators for emotionally high activation, which corresponds with our findings. Consequently, EDA can be used as a reliable measure for emotional activation during learning.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…EDA data followed a significant linear trend corresponding to HR data, which is, considering the self-report results, in line with our second hypothesis. Prior research (e.g., Eteläpelto et al, 2018 ; Kreibig, 2010 ) showed that high EDA values are indicators for emotionally high activation, which corresponds with our findings. Consequently, EDA can be used as a reliable measure for emotional activation during learning.…”
Section: Discussionsupporting
confidence: 91%
“…Since we see emotions as a two-dimensional model, both, valence and activation must be examined to capture emotions comprehensively. Then, merging EDA and HR data reveals a physiological pattern, which can identify emotional states (e.g., Barrett & Russell, 1999 ; Eteläpelto et al, 2018 ; Larsen & Diener, 1992 ; Levenson et al, 2017 ). Furthermore, only the valence can declare if the emotion is positive or negative, which is crucial for successful learning.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, at a time when measurement technology, for example, relating to physiological data, has taken huge developmental steps, one can look forward to research designs combining real-time measurements with self-report data in studies on emotions and learning in the workplace (cf. Eteläpelto et al 2018). Indeed, there is growing interest in studies considering, for example, artificial intelligence and learning, which gathers both physiological and behavioural data about emotion.…”
Section: Future Research and Practical Implicationsmentioning
confidence: 99%
“…The link between emotion and learning is widely investigated as emotion is integral to the learning process and influences students’ learning outcomes [ 6 , 7 , 13 , 14 ]. Positive emotions, such as enjoyment or pride, are positively related to learning, whereas negative emotions, such as frustration, tend to have a negative impact on learning [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%